6.4 TRIAL OF INTEGRATED TOBACCO SMOKING CESSATION, EXERCISE AND WEIGHT MANAGEMENT IN PERSONS WITH SERIOUS MENTAL ILLNESS. (9th April 2019) - Daumit, Gail; Cather, Corinne; Dalcin, Arlene; Dickerson, Faith; Wang, Nae-Yuh; Jerome, Gerald; Miller, Edgar; Appel, Lawrence; McCann, Una; Gennusa, Joseph; Goldsholl, Stacy; Cook, Courtney; et al.
Abstract: Background: Tobacco smoking is the single largest contributor to cardiovascular disease and preventable death in persons with serious mental illness (SMI). The majority of smokers with SMI state they would like to quit. Combination pharmacotherapy and behavioral treatment increases abstinence rates in trials but has not been tested or widely used in community settings. In addition, almost all trials of cessation aids to-date in SMI target selected samples of those willing to quit right away, excluding the less motivated. Moreover, weight gain may accompany smoking abstinence, and obesity is already widespread in SMI. Combined health behavior change interventions relevant to a broad spectrum of SMI are urgently needed, especially in those who smoke. The objective of this study is to develop and test an innovative, scalable intervention delivered in a community mental health organization setting that builds on smoking cessation interventions shown to be effective in trials, and aims to promote prolonged smoking abstinence, improved physical activity and weight control. Methods: The TRIUMPH Trial is a community mental health organization-based, two-arm randomized clinical trial that will test the hypothesis that an 18-month comprehensive, practical tobacco smoking cessation program integrating exercise and weight counseling will be superior to a treatment as usual (TAU) control in achieving prolonged smoking abstinence, physical fitness and weight maintenance. Participants are adults with SMI attending community mental health organizations who are current tobacco smokers expressing interest in quitting. Participants are stratified by readiness to set a quit date within 1 month or 6 months and randomly assigned to receive: 1) TAU with referral to a quit line or 2) the 18-month intervention that includes: i) group and individual smoking cessation and weight management counseling by a health coach and tailored to participants' readiness to quit; ii) smoking cessation pharmacotherapy, iii) exercise. The primary outcome is 7-day point prevalence smoking abstinence at 18 months in intervention participants compared to TAU. Secondary outcomes include continuous smoking abstinence, weight, and physical fitness. Results: One hundred ninety-two participants are enrolled in this ongoing clinical trial. Baseline results will be presented as well as a detailed intervention description. Conclusions: Improving smoking abstinence, physical activity, and weight is critical to decrease premature mortality in SMI, and will require innovative, integrated interventions in community settings. The TRIUMPH Trial is testing an approach that should reach a broad range of smokers with SMI and be practical to implement.